Subcellular connectomic analyses of energy networks in striated muscle - Christopher K. E. Bleck (Nature Portfolio, 2018)
Assessing biological circuit connections in single cells has been intractable due to lack of appropriate tools. Here, Bleck et al. develop a method to assess mitochondrial network connectivity in muscle cells and observe clear differences consistent with differing energy requirements.